RETHINKING ISLAM AND MODERNITY - Mahmudi Mahmudi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2012)
The very quick development of age impact on all human life aspects, especially related to the development of thought, religious affairs, diversity and uniformity in a world where all human beings live in. The issues which often arise in the recent years are those related to pluralism and human rights which are widely discussed, especially studies in Indonesia. The impact of the development of age in which people with all different views and thoughts makes pluralism and human rights placed in different positions. Therefore, pluralism and human rights sometimes led to conflict among the members of people in the earth.This paper will give an account of the views Fathi Osman in pluralism and human rights issues are now always be discussion and conversation in the context of Indonesian.This paper will give an explanation of Fathi Osman views on pluralism and human rights issues which today always become a matter of discussion and conversation in the context of Indonesian.             Key words: Rethinking, Modernity, Pluralism, Fathi Osman